Identification of the volatile and nonvolatile constituents of Schinus molle (L.) fruit extracts and estimation of their activities as anticancer agents - Ezzat E. A. Osman, Eman A. Morsi, Mortada M. El-Sayed, Adil Gobouri, El-Sayed S. Abdel-Hameed (Journal of Applied Pharmaceutical Science, 2021)
This work was designed to assess the cytotoxic potential of Schinus molle (L.) fruit extracts and characterization of their chemical composition. The cytotoxicity of S. molle extracts was carried out on hepatoma HepG2 cell line using the Sulforhodamine B method. The volatile constituents of S. molle normal-hexane (n-hexane) extract and the essential oil were identified by gas chromatography-mass spectrometry (GC-MS), whereas the nonvolatile chemical compositions were investigated using the Liquid chromatography-electron spray ionization-mass spectrometry (LC-ESI-MS) technique. The n-hexane extract showed the highest cytotoxic inhibition activity on the HepG2 cell line in a concentration-dependent manner with inhibition concentration (IC50 = 9.75 µg/ml), followed by n-butanol fraction (IC50 = 10.70 µg/ml) and the essential oil (IC50 = 11.90 µg/ml). The GC-MS investigation of the essential oil afforded 50 compounds classified into monoterpenes and sesquiterpenes with different percentiles. The most abundant monoterpenes were α-phellandrene, myrcene, D-limonene, β-phellandrene, and α-pinene. At the same time, the major sesquiterpenes were juniper camphor, guaiyl acetate, γ-gurjunene, α-cadinol, and β-caryophyllene. On the other hand, the LC-ESI-MS investigation of the methanolic extract, n-butanol fraction, and aqueous part led to the identification of 31 phenolic compounds classified as phenolic acids, phenylethanoids, flavonoids, and tannins. These findings demonstrate the remarkable potentiality of S. molle extracts as a valuable source of anticancer capacity.
Keywords: Anticancer, flavonoids, GCMS, LC-ESI-MS, phenolic, Schinus molle.